Kindergarten teacher well-being: is bad stronger than good? - Markus Forster; Christof Kuhbandner (Frontiers in Psychology)
Forster et al. demonstrated that school teachers’ well-being is related to their educational goals and experienced emotions for students showing undesirable behaviors: the higher the goals and the more positive the emotions, the higher the reported well-being. By contrast, the goals and emotions for students showing desirable behaviors was unrelated to school teachers’ well-being. These findings demonstrated that the principle of “bad is stronger than good” extends to the influence of student behavior on school teacher well-being. The present study examined whether this principle also applies to the well-being of kindergarten teachers who typically focus more strongly on the social–emotional development of children. We measured kindergarten teachers’ (N = 250) affective, evaluative, occupational, and psychological well-being using established questionnaires, and their educational goals and experienced emotions for children showing undesirable (e.g., children who provoke others, disrupt activities, cause physical harm) and desirable (e.g., children who share toys, comfort others, tidy up) behaviors using photorealistic pictures. Replicating the pattern observed for school teachers, the higher the goals and the more positive the emotions for children showing undesirable behaviors, the higher the well-being. By contrast, well-being was unrelated to the goals and the positivity of emotions for children showing desirable behaviors. However, the well-being of the kindergarten teachers was not completely unaffected by children showing desirable behaviors, as well-being was higher the higher the emotional arousal was in response to such children. These findings suggest that kindergarten teachers’ well-being could be improved by helping them to set high educational goals and experience more positive emotions for children showing undesirable behaviors, and to experience higher arousal for children showing desirable behaviors.